2011
DOI: 10.1108/09596111111167579
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the key factors affecting behavioral intentions

Abstract: Purpose -This study aimed at investigating factors that contribute to increasing full-service restaurant customers' behavioral intentions. Unlike previous research, this study integrated both affective and cognitive contributors to customer satisfaction and relationship quality in explaining customers' behavioral intentions. Design/methodology/approach -Data were obtained through a questionnaire survey of full-service restaurant customers in a selected US metropolitan area. The data were subjected to structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 76 publications
(129 reference statements)
8
136
2
3
Order By: Relevance
“…For now, there are a few of studies on customer satisfaction as the antecedent of trust and commit (Kim, 2002;Yoo & Park, 2005;Choi, Choi, & Lee, 2007) commitment has no significant impact on purchase intention of social shopping. This contradicts with Jani and Han (2011) who stated that commitment is a determinant of behavioral intentions. In social shopping, customers may be easier to attain opinions from others, particularly their families and friends.…”
Section: Implications For Academic Researcherscontrasting
confidence: 54%
See 2 more Smart Citations
“…For now, there are a few of studies on customer satisfaction as the antecedent of trust and commit (Kim, 2002;Yoo & Park, 2005;Choi, Choi, & Lee, 2007) commitment has no significant impact on purchase intention of social shopping. This contradicts with Jani and Han (2011) who stated that commitment is a determinant of behavioral intentions. In social shopping, customers may be easier to attain opinions from others, particularly their families and friends.…”
Section: Implications For Academic Researcherscontrasting
confidence: 54%
“…However, most previous studies emphasized mainly on satisfaction (e.g., Jani & Han, 2011;Zeithaml, Berry, & Parasuraman, 1996), trust (e.g., Jani & Han, 2011;Morgan & Hunt, 1994), and/or commitment (e.g., Jani & Han, 2011;Pritchard, Havitz, & Howard, 1999) as predictors of behavioral intentions. Additionally, in recent years, we have witnessed the rapid growth of social shopping in Taiwan, but this growth has generated several transaction-related issues such as no delivery and the delivery of incorrect items as indicated by Kim and Park (2013).…”
Section: Relationship Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is the result of customer satisfaction that can predict the future consumption behaviour of customers (Rajic andDado, 2013, Barber et al, 2011;Jani and Han, 2011;Kangdampully, 1998). Understanding customer behavioural intentions is vital to keeping a relationship with potential customers, which is believed to be the key to the ability of a service provider to generate profits (Zeithaml et al, 1996, Hallowell, 1996Jani and Han, 2011;Kangdampully, 1998). Trying to define customer behavioural intentions after experiencing service, Warshaw and Davis (1985, p.214) stated that it is "the degree to which a person has formulated conscious plans to perform or not perform some specified future behaviour".…”
Section: Customer Satisfaction and Behavioural Intentionsmentioning
confidence: 99%
“…Previous studies have also found that satisfaction is an antecedent of trust (Santos & Porto, 2014;Jani & Han, 2011). So, based on these relationships, it is hypothesized that: emotional, and social value (GLOVAL).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%